Classification Schemes Gone Awry: Implications for Museum Research and Exhibition Display Practices. (24th November 2021) - Mohan, Urmila; Rodgers, Susan
Abstract: Classification schemes for collecting, studying, and displaying objects in museum contexts are power‐filled forms of knowledge in Foucauldian senses. When such typologies are imprecise or, more harmfully, misleading or forthrightly mistaken, a museum's collecting practices, curatorial interpretations, and exhibition display decisions can go astray and obscure the social structural and ideological processes that produced the objects in the first place. This introductory essay explores these issues in general theoretical terms and sets the scene for our special issue's four case studies of historically and ethnographically complex exhibitions in several museums from Manhattan to Brooklyn to Worcester, MA. The literature on the impact of colonialism on museum worlds' systems of thought and classification is especially important. [museum typologies, curatorship, classification schemes]